In vivo Reconstitution of Algal Triacylglycerol Production in Saccharomyces cerevisiae - Hung, Chun-Hsien; Kanehara, Kazue; Nakamura, Yuki (Frontiers in Microbiology, 2016)
The current fascination with algal biofuel production stems from a high lipid biosynthetic capacity and little conflict with land plant cultivation. However, the mechanisms which enable algae to accumulate massive oil remain elusive. An enzyme for triacylglycerol (TAG) biosynthesis in Chlamydomonas reinhardtii, CrDGTT2, can produce a large amount of TAG when expressed in yeast or higher plants, suggesting a unique ability of CrDGTT2 to enhance oil production in a heterologous system. Here, we performed metabolic engineering in Saccharomyces cerevisiae by taking advantage of CrDGTT2. We suppressed membrane phospholipid biosynthesis at the log phase by mutating OPI3, enhanced TAG biosynthetic pathway at the stationary phase by overexpressing PAH1 and CrDGTT2, and suppressed TAG hydrolysis on growth resumption from the stationary phase by knocking out DGK1. The resulting engineered yeast cells accumulated about 70-fold of TAG compared with wild type cells. Moreover, TAG production was sustainable. Our results demonstrated the enhanced and sustainable TAG production in the yeast synthetic platform.